2018
DOI: 10.1007/s00383-018-4269-6
|View full text |Cite
|
Sign up to set email alerts
|

Segmental reversal of distal small intestine in short bowel syndrome: a study on the influence on postoperative weight and intestinal topography in piglets

Abstract: Reversal of a 20-cm distal segment showed no effect on weight gain, but there were some significant histological changes of unknown clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…This study showed, that reversal of a 25 cm long segment of the distal small intestine in our SBS model with excision of 70% of the distal small intestine had a negative effect on weight gain compared to control at a 28 days follow-up. Our results are in concordance to some studies [ 21 25 ] and different from others [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study showed, that reversal of a 25 cm long segment of the distal small intestine in our SBS model with excision of 70% of the distal small intestine had a negative effect on weight gain compared to control at a 28 days follow-up. Our results are in concordance to some studies [ 21 25 ] and different from others [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…In a similar short bowel model with excision of 60% of the distal small intestine length and reversal of 20 cm of the distal small intestine, the weight gain in the group with a reversed segment was 2.31 kg at one month follow-up compared to 2.03 kg in the control group. The difference was not significant [ 21 ]. In another model, small intestine from 150 cm distal to the ligament of Treitz and 150 cm proximal from the ileocecal valve was excised.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First experiments on RS in animals were reported by Mall ( 23 ), but the use of this technique on experimental models of SBS was introduced in the 1950s and 1960s. Many experimental studies with an RS have demonstrated prolongation of transit time, improved absorption, better nutritional status, weight gain, and prolonged survival ( 24 27 ), but other reports have shown no beneficial effects ( 28 30 ). Structural changes like dilatation of the bowel proximal to the RS and increase in muscle thickness, crypt depth, and villus height were described ( 24 , 31 ).…”
Section: Procedures To Slow Intestinal Transitmentioning
confidence: 99%